Platelet-endothelial associations may promote cytomegalovirus replication in the salivary gland in mice. (2nd October 2020) - Braxton, Alicia M.; Chalmin, Alyssa L.; Najarro, Kevin M.; Brockhurst, Jacqueline K.; Johnson, Karl T.; Lyons, Claire E.; Daly, Brenna; Cryer, Catherine G.; Vijay, Shefali; Cyphers, Griffin; Guerrero-Martin, Selena M.; Aston, S. Andrew; et al.
Abstract: Platelet decline is a feature of many acute viral infections, including cytomegalovirus (CMV) infection in humans and mice. Platelet sequestration in association with other cells, including endothelium and circulating leukocytes, can contribute to this decline and influence the immune response to and pathogenesis of viral infection. We sought to determine if platelet-endothelial associations (PEAs) contribute to platelet decline during acute murine CMV (mCMV) infection, and if these associations affect viral load and production. Male BALB/c mice were infected with mCMV (Smith strain), euthanized at timepoints throughout acute infection and compared to uninfected controls. An increase in PEA formation was confirmed in the salivary gland at all post-inoculation timepoints using immunohistochemistry for CD41+ platelets co-localizing with CD34+ vessels. Platelet depletion did not change amount of viral DNA or timecourse of infection, as measured by qPCR. However, platelet depletion reduced viral titer of mCMV in the salivary glands while undepleted controls demonstrated robust replication in the tissue by plaque assay. Thus, platelet associations with endothelium may enhance the ability of mCMV to replicate within the salivary gland. Further work is needed to determine the mechanisms behind this effect and if pharmacologic inhibition of PEAs may reduce CMV production in acutely infected patients.